Pre-eclampsia, eclampsia, and hypertension - Duley, Lelia (BMJ Publishing Group, 2008)
INTRODUCTION: Pre-eclampsia (raised blood pressure and proteinuria) complicates 2-8% of pregnancies, and raises morbidity and mortality in the mother and child. Pre-eclampsia is more common in women with multiple pregnancy and in those who have conditions associates with microvascular disease. METHODS AND OUTCOMES: We conducted a systematic review and aimed to answer the following clinical questions: What are the effects of preventive interventions in women at risk of pre-eclampsia? What are the effects of interventions in women who develop mild-moderate hypertension during pregnancy? What are the effects of interventions in women who develop severe pre-eclampsia or very high blood pressure during pregnancy? What is the best choice of anticonvulsant for women with eclampsia? We searched: Medline, Embase, The Cochrane Library, and other important databases up to June 2007 (BMJ Clinical Evidence reviews are updated periodically, please check our website for the most up-to-date version of this review). We included harms alerts from relevant organisations such as the US Food and Drug Administration (FDA) and the UK Medicines and Healthcare products Regulatory Agency (MHRA). RESULTS: We found 53 systematic reviews, RCTs, or observational studies that met our inclusion criteria. We performed a GRADE evaluation of the quality of evidence for interventions. CONCLUSIONS: In this systematic review we present information relating to the effectiveness and safety of the following interventions: anticonvulsants, antihypertensive drugs, antioxidants, antiplatelet drugs, atenolol, bed rest, hospital admission or day care, calcium supplementation, choice of analgesia during labour, early delivery (interventionist care), evening primrose oil, fish oil, glyceryl trinitrate, magnesium supplementation, plasma volume expansion, and salt restriction.